Cultural journalism and the professionalization of the writer: An analysis of the chapter “La forja del writer profesional (1900-1930)” by Jorge B. Rivera - da Silva Gomes, Maria Isabela [UNESP] (Universidad Tecnologica de Pereira - UTP, 2023)
This work analyzes the chapter called “La forja del escritor profesional: 1900-1930. Los escritores y los nuevos medios masivos”, by the critic, essayist, and thematic researcher of popular culture Jorge B. Rivera (1935 – 2004), from the approach related to cultural journalism – as one of the needs of the press – and the professionalization of the Argentine writer. On the cusp of the 20th century, the development of the cultural industry and the process of professionalization of the writer in the field of journalism, although in a phase whose copyri-ghts are not recognized, and the editorial structure is still incipient. The public, the existence of new editorial and journalistic means, as well as specialization will be, consequently, the decision-making factors for the configuration and growth of a new type of writer, the professional. For this finding, through the method and historical perspective, this analysis sought to deal with the segmentation and growth of the reading public increa-singly attentive to the subjects of greater depth, corresponding, above all, to the sections on economics, politics and culture. Thus, the historiographic cut-off delimited by the work, demarcating the first 3 decades of the Argentine twentieth century is fruitful for the study of Rioplatense periodicals and for the observation of the flourishing of literary journalism, a field in which writers begin to experience the new possibilities and the limits of professionalization.
Jornalismo cultural e profissionalização do escritor: Uma análise do capítulo “La forja del escritor profesional (1900-1930)” de Jorge B. Rivera
Keywords: culture; intellectuality; journalism; professionalization